Prevalence of Diagnosis and Staging of Chronic Kidney Disease by Primary Care Providers in a Rural State - Suneetha Muthyala MD; Abe E. Sahmoun PhD; Ketki Tendulkar MBBS; Byron Danielson MD (SAGE Publishing, 2011)
Context: The Kidney Disease Outcomes and Quality Initiative guidelines are the most widely disseminated guidelines regarding the clinical evaluation and management of chronic kidney disease (CKD). Purpose: Assess the prevalence of diagnosis and staging of CKD by primary care providers (PCPs). Methods: For the purpose of this assessment, stage 3 CKD was defined as an estimated glomerular filtration rate (eGFR) between 30 and 59 mL/min/1.73 m 2 for at least 3 months. Eligible individuals were 1447 white, nondiabetic patients 40-74 years of age. Results: Information on a random sample of 110 patients was analyzed. Chronic kidney disease was reported in 22% of the patients, whereas only 7% of patients had both CKD and stage 3 reported in their medical record. PCPs were significantly more likely to record CKD in male than in female patients (79% vs 34%; P < .001). Patients who had CKD recorded were significantly more likely to be referred to a nephrologist (46% vs 3%; P < .001). Even among patients who had a diagnosis of coronary artery disease, were older, or had lower eGFR, a diagnosis of CKD was less likely to be recorded. Only 22% had their serum phosphorus, 12% their parathyroid hormone, and 64% a urinalysis recorded. Conclusions: This study found that the prevalence of recording CKD and staging by PCPs was low. Primary care providers were more likely to record CKD in male than in female patients. Finally, testing for bone disease is underperformed. There is a need to identify mechanisms to improve evaluation and management of CKD by PCPs.